Palace of Prince Schwarzenberg - Huquier, Jacques-Gabriel, 1725-1805 (engraver):::Creator:::::::::::: (Paris; France; Huquier fils, Graveur)
Color vue d'optique engraving of the Schwarzenberg Palace in Vienna; intended for viewing through an optical machine such as a zograscope or peep box with a curved lens and mirror that makes the print appear to be three-dimensional